Potential Alternative Tree Species as Substrates for Forest Farming of Log-grown Shiitake Mushrooms in the Southeastern United States - Gregory E. Frey; Tarik Durmus; Erin O. Sills; Fikret Isik; Marcus M. Comer (HortTechnology, 2020)
Shiitake (Lentinula edodes) is an edible mushroom-producing fungus. “Natural log-grown” shiitake mushrooms are favored by consumers and are often produced by small farmers and hobbyists in the United States. The tree species most often recommended as a substrate for shiitake is white oak (Quercus alba), which has many other economic uses. We tested two strains of shiitake in log substrates of three common, low-value tree species in the southeastern United States to identify potential alternatives to white oak. We found that sweetgum (Liquidambar styraciflua) was a good substitute for white oak, both in terms of mushroom production and financial returns. Red maple (Acer rubrum) had less potential, with lower production and marginal financial returns, and ailanthus (Ailanthus altissima) was not a suitable alternative substrate. Of the two shiitake strains tested, a commercially available strain performed better than a naturalized strain that was isolated from an uninoculated log. Further research is needed to identify other potential alternative substrates and production techniques in the southeastern United States and other regions.